Urbanisation and its associated factors affecting human gut microbiota: where are we heading to? - Farhat Abjani; Priya Madhavan; Pei Pei Chong; Karuthan Chinna; Charles Anthony Rhodes; Yvonne Ai Lian Lim (Annals of Human Biology, 2023)
Context The continuous rise in urbanisation and its associated factors has been reflected in the structure of the human gut ecosystem. Objective The main focus of this review is to discuss and summarise the major risk factors associated with urbanisation that affect human gut microbiota thus affecting human health. Methods Multiple medical literature databases, namely PubMed, Google, Google Scholar, and Web of Science were used to find relevant materials for urbanisation and its major factors affecting human gut microbiota/microbiome. Both layman and Medical Subject Headings (MeSH) terms were used in the search. Due to the scarcity of the data, no limitation was set on the publication date. Relevant materials in the English language which include case reports, chapters of books, journal articles, online news reports and medical records were included in this review. Results Based on the data discussed in the review, it is quite clear that urbanisation and its associated factors have long-standing effects on the human gut microbiota that result in alterations of gut microbial diversity and composition. This is a matter of serious concern as chronic inflammatory diseases are on the rise in urbanised societies. Conclusion A better understanding of the factors associated with urbanisation will help us to identify and implement new biological and social approaches to prevent and treat diseases and improve health globally by deepening our understanding of these relationships and increasing studies across urbanisation gradients.HIGHLIGHTS Human gut microbiota have been linked to almost every important function, including metabolism, intestinal homeostasis, immune system, biosynthesis of vitamins, brain processes, and behaviour. However, dysbiosis i.e., alteration in the composition and diversity of gut microbiota is associated with the pathogenesis of many chronic conditions. In the 21st century, urbanisation represents a major demographic shift in developed and developing countries. During this period of urbanisation, humans have been exposed to many environmental exposures, all of which have led to the dysbiosis of human gut microbiota. The main focus of the review is to discuss and summarise the major risk factors associated with urbanisation and how it affects the diversity and composition of gut microbiota which ultimately affects human health.